Genentech Immunology & Ophthalmology (GIO) : culture change to drive business results (A) - Chatman, Jennifer, (SAGE Knowledge. Cases., 2017)
This case study provides the story of Jennifer Cook, Senior Vice President of the Immunology and Ophthalmology (GIO) business unit at Genentech who had worked hard with her team from 2010-2012 to develop a cohesive culture to tie together GIOs four brands, as she believed that culture fundamentally would drive the performance of her group and it was too important to leave to chance. In the process, she had faced a series of pressing questions such as how to bring her team together; what might affect the groups performance; what features of culture were at play; and what stood in the way of positive change? This case study provides students an opportunity to see first-hand what Cook and her team came up with and how they implemented a very successful culture change process. The (B) case allows students to discuss performance measurement and what the team should do next.